Islam dan Pluralitas Agama (Studi Analisis tentang Model Pendekatan dalam Dialog Antar Umat Beragama di Indonesia) - Andi Jufri (Jurnal Ilmiah AL-Jauhari: Jurnal Studi Islam dan Interdisipliner, 2019)
The plurality of religion is an inevitable phenomenon, and every religion emerges in a plural environment. If the pluralistas of these religions are not addressed appropriately, they will potentially lead to problems of vulnerability and conflict between religious communities, and this fact has already happened to monotheistic religions. To find a solution to the conflict between religious communities there needs to be the right approaches. What are the approaches used in efforts to break up conflicts between religious believers? This paper wants to uncover the problem of religious plurality in Indonesia and several approaches that can be used as role models in building dialogue between religious communities.